2022
DOI: 10.5430/wjel.v12n7p106
|View full text |Cite
|
Sign up to set email alerts
|

Students' Attitudes to the Implementation of Vocabulary Learning Strategies in Writing Task

Abstract: Saudi Arabia is an extraordinary intermingling between religion and culture. Based on their religion and culture Saudi Arabia women’s met challenges for the public authority over education system. In Arabic countries male dominance and feminisms plays equal roles in order to overcome it the women’s should come front to stand their rights. The place of ladies in this general public is confounded and they need to confront a great deal of obstructions to get instruction as they live under male power constantly. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…On the contrary, the high achievers disfavor asking teachers to check the student word lists (M=1.11), and the low achievers dislike using the semantic feature grids (M=1.06). Meanwhile, Ali et al (2022) found that students at a technical university in Malaysia used vocabulary learning strategies at a moderately low level of intensity. These studies indicate that more research is still required to broaden our repertoire of the pattern of strategy used by different groups of learners.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the high achievers disfavor asking teachers to check the student word lists (M=1.11), and the low achievers dislike using the semantic feature grids (M=1.06). Meanwhile, Ali et al (2022) found that students at a technical university in Malaysia used vocabulary learning strategies at a moderately low level of intensity. These studies indicate that more research is still required to broaden our repertoire of the pattern of strategy used by different groups of learners.…”
Section: Introductionmentioning
confidence: 99%